PROBLEMS OF TRANSLATION FROM ENGLISH INTO INDONESIAN OF THE NOVEL EAT PRAY LOVE - Susana R. Bahara (Universitas Khairun, 2021)
The aims of this research are to find out what the inaccuracies in the translation of words, phrases, and sentences from English into Indonesian of the novel EAT PRAY LOVE and what Factors lead to those inaccuracies. This research employs descriptive method and qualitative approach approach proposed by Cresswell and Lodico at al. The key instrument in this research is the researcher herself. The data of this research are obtained from both the original and the translation of the novel EAT PRAY LOVE, which consists of the inaccuracies in the translation of words. Based on the data, the researcher finds quite of few inaccuracies in the translation of words, phrases, and sentences, which the problems findings are the tendency in using free translation which it caused the translator sometimes give addition, omission, and substitution in the translation, and the inaccuracy in choosing equivalent that sometimes make the translation sound unnatural. This indicates that (a) the translator fails to find the good equivalents. (b) The loss of concentration and carefulness while translating. (c) Misinterpretation of the meaning and the message in the source text. (d) unfamiliar with idioms/expression. (e) miscomprehention of the English sentence structure, especially complex sentences and noun phrases. (f) Misuse of omission, addition, and substitution strategy in the translation. (g) Miscomprehention of the theory of translation.